PHYTOTHERAPY HAS POTENTIAL EQUIVALENT TO ANTIBIOTIC THERAPY FOR CLEARING THE ENDOMETRITIS IN CROSSBRED CATTLE - TOMAR, SS; SUDERSHAN,; BHARADWAZ, A; NEMA, SP; RAJPUT, N (The Indian Journal of Animal Reproduction, 2017)
Twenty-four endometritic-crossbred cattle were equally divided to receive, once a day, 15 ml normal saline, ciprofloxacin, neem or garlic as intrauterine treatment at estrus. At post-treatment estrus, the majority of cattle treated with antibiotic or herbal extracts had similar recovery (p>0.05) evidenced on the basis of clear mucus discharge, negative white side test and cervical mucus pH. Thus, the herbal extract therapy (phytotherapy) can be explored for the treatment of endometritis in crossbred cattle.
Keywords: Endometritis; Garlic; Neem; pH; White side test